Infecções por bactérias gram negativas em pacientes com tumor sólido ou doença hematológica maligna internados em unidade de tratamento intensivo pediátrico: desfecho clínico e fatores associados a multirresistência - Costa, Patrícia de Oliveira (2014)
This study aimed at evaluating the predictors associated with multidrug-resistant Gram-negative bacterial (MDR- GNB) infections and the predictors of 7- and 30-day mortality in pediatric patients with cancer and/or hematologic diseases and Gram-negative bacteria (GNB) infection hospitalized in a pediatric intensive care unit (ICU). Methods Data were collected relating to all episodes of GNB infection that occurred in a pediatric ICU between January 2009 and December 2012.The GNB infections were divided into 2 groups for comparison: 1) infections attributed to multidrug resistant Gram negative bacteria and 2) infections attributed to susceptible Gram negative bacteria. Furthermore, these episodes of were divided into 2 groups: those who were deceased 7- and 30- days after the date of positive culture. Variables of interest included age, gender, presence of solid tumor or hematologic disease, cancer status , central venous catheter use, previous Pseudomonas aeruginosa infection, infection MDR- GNB, colonization by MDR-GNB, heathcare associated infection, neutropenia in the preceding 7 days, duration of neutropenia,length of hospital stay before ICU admission, length of ICU stay, appropriate antimicrobial treatment, definitive inadequate antimicrobial treatment, time to initiate adequate antibiotic therapy, duration of antibiotic therapy, shock, 7- and 30-day mortality.. In addition, the use of antimicrobial agents, corticosteroids, chemotherapy, or radiation therapy in the previous 30 days was noted. Results Multivariate logistic regression analyses showed significant relationships between MDR-GNB and hematologic diseases (odds ratio [OR] 5.262; 95% confidence interval [95% CI] 1.282 21.594; p=0.021), and heathcare-associated infection (OR 18.360; 95% CI 1.778 189.560; p=0.015). Multivariate logistic regression analyses resulted in significant relationships between shock and both, 7-day mortality (OR 12.397; 95% confidence interval [95% CI] 1.291 119,016; p=0.029) and 30-day mortality (OR 6.174; 95% CI 1.760 21.664; p=0.004), between duration of antibiotic therapy and 7-day mortality (OR 21.328; 95% CI 2.834 160.536; p=0.003), and between colonization by MDR-GNB and 30-day mortality (OR 12.002; 95% CI 1.578 91.286; p=0.016). Conclusions Hematologic malignancy and heathcare-associated infection were significantly associated with MDR-GNB infection in this sample of pediatric oncology patients.